Late diagnosis of severe long-standing autoimmune hypothyroidism after the first lockdown for the Covid-19 pandemic: clinical features and follow-up - Mansueto, Morena Luce; Zagni, Giulia; Sartori, Chiara; Olivares Bermudez, Bernardo Antonio; Righi, Beatrice; Catellani, Cecilia; Fusco, Carlo; Frasoldati, Andrea; De Fanti, Alessandro; Iughetti, Lorenzo; Street, Maria Elisabeth (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Hashimoto’s thyroiditis (HT) is a common endocrinopathy in children, particularly in females. Clinical overt presentation of hypothyroidism in HT includes mild to very severe forms, characterised by impairment of many body functions and organs, such as heart, brain, muscles, ovaries and liver. Case: we report the case of a 14-year-old girl, with severe hypothyroidism due to a late diagnosis of HT during the Covid-19 pandemic. Routine biochemical and hormonal exams were carried out at presentation. Moderate pericardial effusion was detected by echocardiography and polycystic ovarian morphology (PCOM) was found on the pelvic ultrasound. Furthermore, high levels of creatine phosphokinase (CPK), Lactic Acid Dehydrogenase (LDH) and hepatic liver enzymes, associated with muscular pseudohypertrophy and bilateral weakness of the lower limbs, were suggestive of a rare presentation of long-standing hypothyroidism defined Kocher-Debre-Semelaigne syndrome (KDSS). Levothyroxine replacement therapy was started immediately, leading to a rapid improvement of symptoms and a progressive normalization of the biochemical parameters. Due to persistent lower limb weakness, further neurological investigations were performed, showing bilateral peripheral polyneuropathy (PNP), ascribable to the longstanding and severe hypothyroidism. A pelvic ultrasound, performed after thyroid hormones had normalised and menses had turned to be regular, showed normal ovarian features supporting the hypothesis of the Van Wyk and Grumbach syndrome in a post-menarcheal girl. Conclusions: although clinical manifestation of hypothyroidism are usually mild, more severe and rare presentations such as ovarian dysfunction and myopathy are possible, particularly if the diagnosis is delayed and replacement therapy is not promptly administered.